2019
DOI: 10.1080/03079457.2019.1677856
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on transmissible viral proventriculitis and chicken proventricular necrosis virus (CPNV) in the UK

Abstract: Chicken proventricular necrosis virus (CPNV) is a recently described birnavirus, which has been proposed to be the cause of transmissible viral proventriculitis (TVP). The understanding of the epidemiology of both the virus and the disease is very limited. A retrospective investigation on TVP and CPNV in broiler chicken submissions from the UK from between 1994 and 2015 was performed with the aims of assessing the longitudinal temporal evolution of TVP and CPNV and to review the histological proventricular les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…Recent research from the UK also suggests the involvement of CPNV in the development of TVP in chickens. In two studies, the authors reported that CPNV was detected in 22 and 47% of con rmed clinical cases of TVP [11,12]. It remains unknown, however, if all cases of this disease are of the same infectious origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research from the UK also suggests the involvement of CPNV in the development of TVP in chickens. In two studies, the authors reported that CPNV was detected in 22 and 47% of con rmed clinical cases of TVP [11,12]. It remains unknown, however, if all cases of this disease are of the same infectious origin.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unknown, however, if all cases of this disease are of the same infectious origin. There are cases of TVP in which CPNV cannot be identi ed, as well as disease cases in which CPNV can be identi ed but which do not meet the diagnostic criteria of TVP [7,11,12]. In addition, it is suggested that the pathogenesis of TVP could be more complex and may result from other viral, bacterial or fungal co-infections [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent research, intranuclear inclusion bodies were observed in case of the submissions with TVP. The vast majority of these cases gave negative CPNV RT-PCR results, raising the question of whether another virus different from CPNV is responsible for some of these TVP-affected cases ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of TVP has not been explicitly defined so far. Studies on TVP etiopathology imply the involvement of infectious bursal disease viruses (IBDV) of the Birnaviridae family, IBDV-like viruses, infectious bronchitis viruses (IB) of the Coronaviridae family, reoviruses (REO), picornaviruses, fowl adenoviruses (FAdV), adeno-like viruses, or mixed infections in the development of typical pathological lesions [ 3 , 4 , 5 , 6 , 8 , 10 , 11 , 12 , 13 , 14 , 15 ]. Recently, a novel virus identified as a member of the Birnaviridae family has been isolated from clinical cases of TVP.…”
Section: Introductionmentioning
confidence: 99%